Implikasi Keberadaan Reforma Agraria dalam Menekan Konflik Agraria di Indonesia - Yoseva Pratiwi Simamora (Jurnal Hukum Lex Generalis, 2025)
One of Indonesia's issues is agrarian strife. In an attempt to settle land conflicts, this research looks at the causes of agricultural conflict as well as the idea of ​​agrarian reform. Using a Normative Juridical methodology, the study demonstrates that social, cultural, economic, and political structural conflict concerns are almost invariably linked to agricultural conflict. Restructuring the ownership, management, and utilization of agricultural resources for the benefit of the general public (farmers, farmworkers, the homeless, and others) is known as agrarian reform. The goal of agrarian reform is to resolve the disputes and inequities that occur.